What Contributes to Students’ Success in Learning to Speak English - Sartika; Amin, Muhammad (JEELS (Journal of English Education and Linguistics Studies), 2014)
This study deals with speaking achievement of eighth semester students in English Department of one university in Nusa Tenggara Barat - Indonesia in academic year 2013/2014. The purpose of this study was to find out factors that help students succeed in learning speaking. The method of this research is qualitative research that focuses on case study. The subjects of this study were the eighth semester students who got an A in Speaking I, II and III subjects. Four students were recruited as the research subjects consisting of one female and three males. The data about the students were obtained from the academic databases in the English Department. In collecting the data, semi-structured interviews were conducted. The data, then, were analyzed through some stages namely transcribing data, reducing data, displaying data and drawing conclusion. The result of this study showed that factors contributing to students speaking achievement consist of internal and external factors. The internal factors include motivation and interests, while the external factors involve family, school condition and society.